2017
DOI: 10.1002/ece3.2987
|View full text |Cite
|
Sign up to set email alerts
|

World without borders—genetic population structure of a highly migratory marine predator, the blue shark (Prionace glauca)

Abstract: Highly migratory, cosmopolitan oceanic sharks often exhibit complex movement patterns influenced by ontogeny, reproduction, and feeding. These elusive species are particularly challenging to population genetic studies, as representative samples suitable for inferring genetic structure are difficult to obtain. Our study provides insights into the genetic population structure one of the most abundant and wide‐ranging oceanic shark species, the blue shark Prionace glauca, by sampling the least mobile component of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
54
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 100 publications
7
54
3
Order By: Relevance
“…This lack of genetic differentiation at a wide scale is consistent with the recent reports of genetic homogeneity of this species at a regional scale in the Indo‐Pacific (Ovenden, Kashiwagi, Broderick, Giles, & Salini, ; Taguchi, King, Wetklo, Withler, & Yokawa, ) and in the North Pacific (King et al., ), and at broad scale between Atlantic North and South and between Atlantic and Pacific (Verissimo et al., ) and between Atlantic and Mediterranean Sea (Leone et al., ; but only with mtDNA). This result is as well consistent with the broad‐scale panmixia reported for other widely distributed species, such as lemon sharks (Feldheim, Gruber, & Ashley, ; Schultz et al., ), scalloped hammerhead sharks ( Sphyrna lewini , Ovenden et al., ; Daly‐Engel et al., ), milk sharks ( Rhizoprionodon acutus , Ovenden et al., ), school sharks ( Galeorhinus galeus , Hernández et al., ) and basking sharks ( Cetorhinus maximus , Hoelzel, Shivji, Magnussen, & Francis, ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This lack of genetic differentiation at a wide scale is consistent with the recent reports of genetic homogeneity of this species at a regional scale in the Indo‐Pacific (Ovenden, Kashiwagi, Broderick, Giles, & Salini, ; Taguchi, King, Wetklo, Withler, & Yokawa, ) and in the North Pacific (King et al., ), and at broad scale between Atlantic North and South and between Atlantic and Pacific (Verissimo et al., ) and between Atlantic and Mediterranean Sea (Leone et al., ; but only with mtDNA). This result is as well consistent with the broad‐scale panmixia reported for other widely distributed species, such as lemon sharks (Feldheim, Gruber, & Ashley, ; Schultz et al., ), scalloped hammerhead sharks ( Sphyrna lewini , Ovenden et al., ; Daly‐Engel et al., ), milk sharks ( Rhizoprionodon acutus , Ovenden et al., ), school sharks ( Galeorhinus galeus , Hernández et al., ) and basking sharks ( Cetorhinus maximus , Hoelzel, Shivji, Magnussen, & Francis, ).…”
Section: Discussionsupporting
confidence: 89%
“…Verissimo et al. () reviewed the cosmopolitan coastal pelagic carcharhinoids and oceanic epipelagic sharks for which isolation and lineage divergence have been shown between Atlantic and Indo‐Pacific, probably due to colder water conditions around the tip of South Africa and to the cold Benguela current. These authors concluded that the current apparent genetic homogenization of the species is due to extensive interbasin gene flow since the last glacial period, which may apply the blue shark.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tiger shark displays moderate genetic diversity with a very low number of mitochondrial haplotypes and haplotype diversity for the sequences studied compared to other shark species, such as the bull shark Carcharhinus leucas (Pirog, Jaquemet, et al, ), the great white shark Carcharodon carcharias (Pardini et al., ), the blue shark Prionace glauca (Veríssimo et al., ), the blacktip reef shark Carcharhinus melanopterus (Vignaud et al., ), or the tope shark Galeorhinus galeus (Chabot, ; Chabot & Allen, ). Furthermore, using the same protocol on the same date from extraction to marker testing for polymorphism, we characterized 20 microsatellite loci for the bull shark (Pirog et al., ), and only eight for the tiger shark (Pirog et al., ), which supports a lower genetic diversity in the latter species.…”
Section: Discussionmentioning
confidence: 96%
“…Notable examples include the pan‐Atlantic movements of spurdogfish Squalus acanthias L. 1758 (Holden, ), white Carcharodon carcharias (L. 1758) (Skomal et al ., ) and porbeagle Lamna nasus (Bonnaterre 1788) sharks (Cameron et al ., ). Genetic approaches suggest that ocean scale‐mixing may also be common for other large shark species, including both blue Prionace glauca (L. 1758) (Veríssimo et al ., ) and basking sharks Cetorhinus maximus (Gunnerus 1765) (Hoelzel et al ., ).…”
mentioning
confidence: 99%